Компенсация систематических погрешностей тонкопленочных элементов через элементы фотошаблона - Spirin, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Several methods are considered for compensating for systematic errors in the design parameters of thin-film resistors that determine the yield of functional microassemblies. A method of compensation is proposed by modifying the dimensions of photomask elements according to specific algorithms, which will allow for a significant reduction in the dimensions of all thin-film elements without reducing the yield percentage of functional microassemblies.